SARP research proceedings : (Tamil Nadu Agricultural University, 1995)
The study offered a unique opportunity to assess the growth of one rice cultivar on different soil types, under different weather conditions, and at N application levels. The seed source, date of sowing and planting, treatments and general agronomic practices were identical for al sites and adequate crop protection measures were taken.